1997
DOI: 10.2307/4065272
|View full text |Cite
|
Sign up to set email alerts
|

The Links between Legal Status and Environmental Health: A Case Study of Mozambican Refugees and Their Hosts in the Mpumalanga (Eastern Transvaal) Lowveld, South Africa

Abstract: This article relates the legal status of Mozambicans in South Africa from 1985 onwards to key findings of a demographic census taken in 1992, an environmental health survey conducted in 1993, and in-depth fieldwork in some of the surveyed settlements in 1995. The case study area on the border with Mozambique is typical of South Africa's rural former homelands, with the exception that it has a large and long-standing refugee population. The environmental health indicators for refugees are considerably worse tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…Though the situation is changing, people in these villages have lived with limited legal recognition without fully being integrated into South African society. The villages have poor dwellings and infrastructure and are worse off than mainly South African villages with respect to basic services including water, sanitation, electricity and health facilities [44,45]. Other researchers in the study area have also found poorer health outcomes in children living in former Mozambican households [46].…”
Section: Discussionmentioning
confidence: 99%
“…Though the situation is changing, people in these villages have lived with limited legal recognition without fully being integrated into South African society. The villages have poor dwellings and infrastructure and are worse off than mainly South African villages with respect to basic services including water, sanitation, electricity and health facilities [44,45]. Other researchers in the study area have also found poorer health outcomes in children living in former Mozambican households [46].…”
Section: Discussionmentioning
confidence: 99%
“…Despite voluntary repatriation programmes following a formal peace agreement in 1992, it was estimated that by 2000 that more than 200,000 former Mozambican refugees were still living in the province (Johnston, 2000). They have remained a poorer and more vulnerable group, living in isolated villages with less or weaker infrastructure, poor access to water and sanitation, generally further away from health facilities and labour markets, with limited legal rights and experience barriers to accessing social grants, education and health services (Dolan et al, 1997, Hargreaves et al, 2004; Kahn, 2008). Hargreaves and colleagues (2004) have demonstrated higher mortality rates among children from Mozambican-headed households when compared to South African-headed households; lack of legal status and poorer SES of many former Mozambican refugees partly explains this disparity.…”
Section: Discussionmentioning
confidence: 99%
“…Our results show that there was a persistent (constant) wealth (SEP) gap between former refugee and South African households despite the fact that former refugee households had slightly higher asset accumulation rates in terms of the number of assets (Table ). In this respect, the refugees arrived with very few assets (Dolan et al ., ; Rodgers, ) and were unable to close the wealth gap because their asset accumulation rate was influenced by lower return strategies levied off a lower initial asset base. The longā€term effect of a low initial asset status (Barrett, ), therefore, continues to affect their asset accumulation rate despite having arrived over 20 years ago (Schatz, ; Collinson, ).…”
Section: Discussionmentioning
confidence: 99%